2013
DOI: 10.1186/1756-9966-32-100
|View full text |Cite
|
Sign up to set email alerts
|

XAV939, a tankyrase 1 inhibitior, promotes cell apoptosis in neuroblastoma cell lines by inhibiting Wnt/β-catenin signaling pathway

Abstract: BackgroundNeuroblastoma (NB) is the most common extracranial solid tumor in childhood. The present treatment including surgery, chemotherapy and radiation, which have only 40% long-term cure rates, and usually cause tumor recurrence. Thus, looking for new effective and less toxic therapies has important significance. XAV939 is a small molecule inhibitor of tankyrase 1(TNKS1). The objective of this study is to investigate the effect of XAV939 on the proliferation and apoptosis of NB cell lines, and the related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 34 publications
1
76
0
Order By: Relevance
“…Previous studies showed that treatment of human mesenchymal stromal cells with XAV939 significantly decreased ALP activity [24]. Moreover, XAV939 induced cell apoptosis in neuroblastoma cells [25]. Here, we treated HAVICs with XAV939 and found that the latter dose-dependently decreased the number of HAVICs.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies showed that treatment of human mesenchymal stromal cells with XAV939 significantly decreased ALP activity [24]. Moreover, XAV939 induced cell apoptosis in neuroblastoma cells [25]. Here, we treated HAVICs with XAV939 and found that the latter dose-dependently decreased the number of HAVICs.…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, the therapeutic effect is not satisfactory. Previous studies found that XAV939, a TNKS1 inhibitor, inhibited the proliferation of colon cancer and neuroblastoma (NB) cells, presumably by preventing PARsylation of TRF1 (8) or by inhibiting the Wnt/β-catenin signaling pathway (14,15) and causing a downstream DNA damage response (15,16). At present, it is not clear whether XAV939 affects telomere length and telomerase activity in NB cells.…”
Section: Introductionmentioning
confidence: 78%
“…Studies have shown that targeted inhibition of GSK-3β protein greatly affected cell proliferation and telomere length, suggesting a relationship between telomere maintenance and Wnt signaling pathways (31). Our previous study also demonstrated that XAV939 induced the apoptosis of NB cells as detected by Annexin V and Hoechst 33342 staining as well as decreased expression of Bcl-2 (14). In agreement with previous research, the cell apoptosis was confirmed by TEM and FCM, and decreased invasive ability was detected by invasion assay following XAV939 treatment or RNAi-TNKS1.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations